Japanese Community-Based Farming (Shurakueino): A Perspective for Empowerment of Indonesian Farmer`s Group - Goto, Naoko (Journal of Rural Indonesia [JORI], 2015)
In Indonesia, there are many farmer`s groups. One of them is known as Kelompok Tani which expanded at the time of the Green Revolution in Indonesia. Most recently, the Kelompok Tani is organized under a larger group called the Gapoktan, and, in this era of democratization, manages its own activities as a self-governed organization. However, due to economical, technical, political problems and other factors, they seem like somewhat stagnated. Â As one possible solution to overcome these challenges, this paper attempts to introduce Japanese community-based farming (shurakueino). World War II, especially from the middle of 1950s until the 1970s, Japan experienced high economic growth and became one of the most developed countries in the world. However, rural society started to suffer from many problems from 1970s, such as large scale exodus of the youth from rural to urban areas, aging of the population, decreases in activities of rural society and so on. One of the consequences was stagnation of agriculture production and productivity. Many agricultural lands were abandoned. In this situation, many Japanese farmers made attempts to overcome these problems. One of those actions was community-based farming (shurakueino). This is a farmer`s organization created and managed by local farmers. This organi- zation usually consolidates farmland in the village and cultivates the land with members participating in the community-based farming. These days, such organizations have incorporated, becoming companies that can manage production, processing, distribution, and sales on its own. They also work on activities unrelated to farming with other villagers. Every organization has a different strategy to improve its farming and the com- munity in their village through community-based farming. This paper shows my observation on the three cases of successful community farming organization Tagirinosan, Kitanohara, and Sunfarm Hoyoji, in Na- gano, and Shiga prefecture. This paper intends to introduce a case study of Japanese farming organizations to show a perspective for the empowerment of Indonesian farmer`s group.Keywords: farmer`s group, community-based farming, self-governed organization